THE IMPACT OF STOCK PRICE VOLATILITY ON THE PERFORMANCE OF THE NIGERIAN STOCK MARKET FOR THE PERIOD 1990 TO 2011 - Cornelius, Ojong M.; Ogar, Anthony; UDOKA, CHRIS O. (Archives of Business Research, 2015)
Abstract This study examines the impact of stock price volatility on the performance of the Nigerian stock market for the period 1990 to 2011. To achieve this objective data were gathered on macroeconomic variables such as stock price volatility, market capitalization, exchange rate, interest rate and inflation rate were captured for the purpose of analysis. The data were tested using the Elliot-Rothernberg-Stock Test, the Generalised Autoregressive Conditional Heteroskedasticity (GARCH) Test and the Granger Causality Test. The multivariate Johansen Cointegration Test was performed to establish the long run relationship among the variables. The Vector Error Correction Mechanism (VECM) under the framework of Vector Autoregressive (VAR) Model was used to estimate the short run relationship. The result of the GARCH test showed that volatility shocks in the Nigerian stock market were not quite persistent during the study periods. The result of the Cointegration test revealed that there exist long-run relationships among the variables in the model. The result of the Granger Causality test showed that stock price volatility granger caused market capitalization in Nigeria. The result of the short run estimation showed that stock price volatility is negatively related to stock market performance. It is recommended that there is need to ensure stability of the stock market, so as to boost and restores investors confidence in the market. Such confidence will lead to increased investment in the market.